2005
DOI: 10.1007/s10803-005-5035-x
|View full text |Cite
|
Sign up to set email alerts
|

Examining the Relationship between Executive Functions and Restricted, Repetitive Symptoms of Autistic Disorder

Abstract: The executive function theory was utilized to examine the relationship between cognitive process and the restricted, repetitive symptoms of Autistic Disorder (AD). Seventeen adults with AD were compared to 17 nonautistic controls on a new executive function battery (Delis-Kaplin Executive Function Scales). Restricted, repetitive symptoms were measured by a variety of instruments (i.e., the Autism Diagnostic Observation Schedule, Autism Diagnostic Interview-Revised, Gilliam Autism Rating Scale, and the Aberrant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

34
378
10
18

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 477 publications
(440 citation statements)
references
References 63 publications
34
378
10
18
Order By: Relevance
“…Deficient performance: Goldstein et al (2001) and Minshew et al (2002). Remark: Both studies showing a deficient performance in ASD only looked at the performance on part B, without controlling for group differences on part A. e Lopez et al (2005). with ASD compared to typically developing controls.…”
mentioning
confidence: 99%
“…Deficient performance: Goldstein et al (2001) and Minshew et al (2002). Remark: Both studies showing a deficient performance in ASD only looked at the performance on part B, without controlling for group differences on part A. e Lopez et al (2005). with ASD compared to typically developing controls.…”
mentioning
confidence: 99%
“…Finally, because EF deficits might correlate with restricted and repetitive behaviors in autism (16), an exploratory region of interest (ROI) analysis examined the relationship between blood oxygen level dependent (BOLD) signal change to target stimuli and the severity of restricted, repetitive behaviors (RRB) for the HFA participants. Regions were selected on the basis of imaging results from a previous study using this task (28) and consisted of the DLPFC (Brodmann area [BA] 9 and 46), ventrolateral prefrontal cortex (VLPFC), the anterior cingulate cortex (ACC; BA 24 and 32), the intraparietal sulcus (IPS) within posterior parietal cortex (PPC), and the basal ganglia (BG).…”
Section: Functional Image Analysismentioning
confidence: 99%
“…Individuals with autism perform poorly on certain tests of EF, such as the Tower of London (TOL), Wisconsin Card Sorting Test (WCST), and extradimensional shifts in the Cambridge Neuropsychological Test Automated Battery (CANTAB) (5,(7)(8)(9)(10)(11)(12)(13). Although not all studies have found EF deficits in ASD (13)(14)(15), impairments seem to be most profound and universal in the domains of cognitive flexibility, set shifting, and inhibition of prepotent responses (5,7,8,16,17). Poor performance on these measures and related EF tasks has also been observed in individuals with damage to the frontal lobes (18,19) or the basal ganglia (20,21), suggesting that these regions are critical for intact EF abilities.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Whilst there has been some debate on the issue (White, 2013), converging evidence suggests that individuals with autism spectrum disorders also show deficits in measures of shifting (Russo, Flanagan, Iarocci, Berringer, Zelazo & Burack, 2007). Importantly, performance on shifting tasks has been associated specifically with the repetitive /restricted preferences domain of autism spectrum behavior; a domain which comprises the preference for predictability (D'Cruz et al, 2013;Lopez et al, 2005). These data suggest that the preference for predictability observed across several neurodevelopmental disorders -even those with distinctly different causes and phenotypesmay be associated with the same cognitive features.…”
Section: Introductionmentioning
confidence: 99%